2020
DOI: 10.1371/journal.pone.0244293
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic roles of diabetes mellitus and hypertension in advanced hepatocellular carcinoma treated with sorafenib

Abstract: Background & aims It remains limited whether diabetes mellitus (DM) and hypertension (HTN) affect the prognosis of advanced hepatocellular carcinoma (HCC) treated with sorafenib. Our study attempted to elucidate the roles of DM/HTN and the effects of diabetes medications among advanced HCC patients receiving sorafenib. Methods From August 2012 to February 2018, 733 advanced HCC patients receiving sorafenib were enrolled at China Medical University, Taichung, Taiwan. According to the presence/absence of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…The associations of high AFP level and Child-Pugh B or C with low OS in our patients were not a surprise. High AFP level was previously associated with low survival rates in patients with HCC induced mainly by HBV and/or HCV treated with sorafenib [13,14,16,18,19]. Previous studies have shown that the time required for the tumor to double in volume, as well as the time for AFP levels to double, were shorter in HCC with higher degrees of malignancy [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The associations of high AFP level and Child-Pugh B or C with low OS in our patients were not a surprise. High AFP level was previously associated with low survival rates in patients with HCC induced mainly by HBV and/or HCV treated with sorafenib [13,14,16,18,19]. Previous studies have shown that the time required for the tumor to double in volume, as well as the time for AFP levels to double, were shorter in HCC with higher degrees of malignancy [37].…”
Section: Discussionmentioning
confidence: 99%
“…DM predicted a better prognosis in HCC treated with sorafenib in two studies [19,20]. Since hyperglycemia favors glycolysis which is a main energy-producing process in cancer cells [35], the authors attributed the association of DM2 with longer survival of HCC patients treated with sorafenib to the effects of TKIs in glycemic control in diabetics reducing proliferation of the malignant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many risk determinants of HCC have already been discussed such as the etiology of cirrhosis, age, gender, race, body mass index (BMI), diabetes, and hepatitis C virus (HCV) genotype [ 4 ]. The occurrence of HCC in diabetes mellitus is most likely related at both molecular and epidemiological levels [ 5 ]. A recent study evidenced that diabetes is associated with a three-fold higher risk for HCC in NAFLD [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Geriatric patients who have a low level of serum albumin should be carefully monitored for HCC [ 1 ]. Elderly people have been correlated with HCC incidence which shows the importance of comorbidity management because of the greater incidence of comorbidities, such as diabetes mellitus and hypertension, in the older population [ 5 ]. In 2018, neoplasm in the liver is found as the sixth most frequent and prevailing cause of cancer-related deaths globally with approximately 841,000 new cases and 782,000 deaths in which HCC is the most common [ 5 ].…”
Section: Introductionmentioning
confidence: 99%